The COVID-19 – related problems encountered by nursing homes in Poland and the steps undertaken to prevent disease spread in the first phase of the epidemic - Nieradko-Iwanicka, Barbara; Iwanicki, Janusz; Dyczewski, Blazej; Herbet, Mariola (Current Issues in Pharmacy and Medical Sciences, 2021)
Nursing Homes (NHs) are institutions of social assistance run by local governments or non-government organizations. Their purpose is to provide individuals with basic services. On March 20, 2020, the Regulation of the Minister of Health issued the declaration of the COVID-19 epidemic in Poland. The introduction of legal regulations allowed the authorities to take actions to prevent infections at NHs. The aim of the study was to analyze the COVID-19 – related problems encountered by nursing homes in Poland and the steps undertaken to prevent disease spread in the first phase of the epidemic. The survey was conducted with use of an original questionnaire e-mailed to 532 NHs throughout Poland in May 2020. Results were analysed by way of the IBM SPSS Statistics program. A total of 89 completed questionnaires were received from: 40 NHs organized by local government (44.9%), 24 run by churches (27.0%), 13 established by non-governmental organizations (14.6%) and 12 operating privately (13.5%). Among them, 78 NHs had less than 100 employees (87.6%) and 11 had more than 100 employees (12.4%), while 68 had up to 100 inhabitants (76.4%) and 21 had more than 100 inhabitants (23.6%). All NHs had problems with recruiting and retaining enough nursing staff. The most commonly used method of COVID-19 spread prevention at NHs in the first phase of the pandemic was establishing an increased sanitary regime, monitoring of temperature of residents and staff members and preparing isolation rooms. The greatest problem was personnel shortages.